2013
DOI: 10.1016/j.drugalcdep.2013.07.024
|View full text |Cite
|
Sign up to set email alerts
|

The group II metabotropic glutamate receptor agonist, LY379268, decreases methamphetamine self-administration in rats

Abstract: Background Given the problems associated with the escalation in methamphetamine (METH) use, the identification of more effective treatment strategies is essential. Group II metabotropic glutamate receptors (mGluRs) have been suggested to be a novel therapeutic target for psychostimulant addiction. We sought to test the ability of the selective group II mGluR agonist LY379268 to reduce METH self-administration in rats. Methods Rats were trained to self-administer METH on a progressive ratio (PR) schedule. Ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…For instance, mGlu 5 receptor antagonists produce a dose-dependent decrease in METH SA without affecting food reinforcement, suggesting that mGlu 5 receptors are involved in the reinforcing effects of METH, but not natural rewards (Osborne and Olive, 2008). Similar effects have been reported with the mGlu 2/3 antagonist LY379268 (1R,4R,5S,6R)-4-amino-2-oxabicyclo[3.1.0]hexane-4,6-dicarboxylic acid) (Crawford et al, 2013;Kufahl et al, 2013). The mGlu 5 receptor is also involved in extinction learning, because administration of an mGlu 5 -positive allosteric modulator resulted in more rapid extinction of responding on the active SA lever.…”
Section: Action Of Substituted Amphetamines and Cathinonessupporting
confidence: 58%
“…For instance, mGlu 5 receptor antagonists produce a dose-dependent decrease in METH SA without affecting food reinforcement, suggesting that mGlu 5 receptors are involved in the reinforcing effects of METH, but not natural rewards (Osborne and Olive, 2008). Similar effects have been reported with the mGlu 2/3 antagonist LY379268 (1R,4R,5S,6R)-4-amino-2-oxabicyclo[3.1.0]hexane-4,6-dicarboxylic acid) (Crawford et al, 2013;Kufahl et al, 2013). The mGlu 5 receptor is also involved in extinction learning, because administration of an mGlu 5 -positive allosteric modulator resulted in more rapid extinction of responding on the active SA lever.…”
Section: Action Of Substituted Amphetamines and Cathinonessupporting
confidence: 58%
“…LY379268 and related compounds decrease reinstatement induced by re-exposure to discrete, discriminative, or contextual cues that were previously associated with alcohol (71), heroin (72, 73), cocaine (74, 75), and methamphetamine (76) self-administration. LY379268 also decreases cocaine priming-induced reinstatement in squirrel monkeys (77) and nicotine and methamphetamine self-administration in rats (78, 79). We also found that systemic and central amygdala LY379268 injections decrease incubation of cocaine craving after forced abstinence (80).…”
Section: Discussionmentioning
confidence: 99%
“…For example, LY379268 reduces anxiety-like behavior only in animals with a history of extended access cocaine self-administration (Aujla et al, 2008). Additionally, studies have shown that mGluR2/3 activation attenuates cue-induced reinstatement of cocaine seeking (Baptista et al., 2004; Adewale et al, 2006) and decreases breakpoints on PR reinforcement schedules in animals with escalated cocaine (Hao et al 2010) and methamphetamine intake (Crawford et al, 2013). The current findings are consistent with these previous studies given our observation of reduced breakpoints at both the lower (0.03 mg/kg) and higher (0.30 mg/kg) doses of LY379268 used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings are consistent with these previous studies given our observation of reduced breakpoints at both the lower (0.03 mg/kg) and higher (0.30 mg/kg) doses of LY379268 used in the current study. Interestingly, LY379268 failed to affect responding for food on a PR, suggesting the possibility of a specific effect on cocaine-maintained responding (Crawford et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation